Complete mitochondrial genome of the guava fruit fly, Bactrocera correcta (Diptera: Tephritidae). (1st November 2016) - Liu, Jian-Hong; Xu, Jin; Li, Yong-He; Dan, Wenli; Pan, Yongzhi
Abstract: Bactrocera correcta (Diptera: Tephritidae) is one of the most serious pest insects in south China and surrounding Southeast Asian countries. The family Tephritidae includes over 4257 species distributed worldwide, so the complete mitochondrial genome would be helpful for bio-identification, biogeography and phylogeny. The B. correcta genome consists of 15 936 bp. Annotation indicated that the structure and orientation of 13 protein-coding genes (PCGs), 22 tRNA and 2 rRNA sequences were typical of, and similar to, the ten closely related tephritid species. The nucleotide composition shows heavily biased toward As and Ts accounting 73.2% and exhibits a slightly positive AT skew, which is similar to other known tephritid species and other insects. The phylogenetic tree indicated the presence of three distinct families (Tephritidae, Muscidae, Drosophilidae) in Order Diptera.